Continuing Education Module—Lamaze Parents Magazine: More Than a Giveaway - Hotelling, Barbara A. (2005)
The Lamaze Parents magazine is an annual publication produced by Lamaze International to inform parents and childbirth educators on issues related to healthy birth preparation, normal birth, and parenting. The author of this column introduces teaching strategies for childbirth educators and doulas to use in tandem with the magazine's content in order to enhance their efforts in sharing current, evidence-based information with expectant parents.